Pengaturan Perlindungan Hukum Terhadap Pengguna Jasa Transportasi di Darat atas Kehilangan dan Kerusakan Barang Kiriman - Fatahillah, Fatahillah (Universitas Malikussaleh, 2015)
Under the provisions of law number 22 of 2009 on traffic and road transport in article 193 states the responsibility of transport companies losses. Article 193 mentions the liability rules on compensation of corporate transportation. In the implementation of the transport was not immune from problems, such as broken, lost and late to the purpose it is due to the negligence of the transport or due to circumstances unforeseen for goods shipped to the detriment of the shipper, or may be carrying less attention to security and safety in the transport goods. In the case of dispute resolution to be taken as a result of damage and loss of goods to get right back to efforts to produce a consensus agreement between the parties. The completion of the deliberation will usually produce an agreement with the results of each of the parties mutually beneficial in order to maintain the good name of company transport services and service users are not unduly disadvantaged.